2015
DOI: 10.15406/mojwh.2015.01.00008
|View full text |Cite
|
Sign up to set email alerts
|

Frequency of Insulin Resistance in Egyptian Women with Polycystic Ovary Syndrome

Abstract: Objectives: To evaluate the prevalence of insulin resistance in polycystic ovary syndrome (PCOS) women and to compare the findings (clinical and laboratory) of PCOS in insulin resistance (IR) to non-IR PCOS women. Patients and methods:Fifty PCOS women included in this cross sectional comparative study. Studied women underwent complete physical examination with calculation of BMI, assessment of hirsutism and measurement of blood pressure. Hormonal and lipid profiles of the studied PCOS women also evaluated. Fas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 37 publications
(38 reference statements)
0
4
0
Order By: Relevance
“…6 School of Medicine, Mashhad University of Medical Sciences, Mashhad, Iran. 7 GREENWICH University England, London, England.…”
Section: Abbreviationsmentioning
confidence: 99%
See 3 more Smart Citations
“…6 School of Medicine, Mashhad University of Medical Sciences, Mashhad, Iran. 7 GREENWICH University England, London, England.…”
Section: Abbreviationsmentioning
confidence: 99%
“…Hyperinsulinemia and insulin resistance (IR) are common in PCOS. Mostafa et al found that about 46% of Egyptian PCOS women had IR [4,7]. Insulin disrupts steroidogenesis in the ovary independently from gonadotropin secretion I PCOS [1].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations